Taxonomic studies of the Trichocoleaceae in Southeast Asia II. A new species of Eotrichocolea from Malaysia - Tomoyuki, Katagiri; Monica Suleiman; Hironori, Deguchi (American Bryological and Lichenological Society Inc., 2012)
The formerly monotypic genus Eotrichocolea is enlarged to accommodate E. furukii, a new species from Southeast Asia. Eotrichocolea furukii is characterized by incubous leaf insertion, robust stem without paraphyllia, well-developed stem cortex, heavily thickened walls at the distal ends of terminal cells of cilia, and absence of Acromastigum-type branching.